2017
DOI: 10.23880/whsj-16000104
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Insulin Resistance and Steroid Endometrial Receptors, KI-67 and BCL-2 after Menopause

Abstract: Introduction: After menopause, the distribution of weight gain and fat deposits may be altered, with a predominance of abdominal fat. This fat has been correlated with the appearance of metabolic and neoplastic diseases. In the endometrium, proliferative lesions may be mediated by steroid endometrial receptors. The aim of this study was to evaluate the association between steroid receptors, proliferation and apoptotic factors and the presence of insulin resistance (IR) in women after menopause. Methods: The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, an in vitro study showed that insulin directly stimulates aromatase activity in both endometrial glands and stroma, which strongly suggests that hyperinsulinemia caused by IR predisposes to EC by enhancing endogenous endometrial estrogen production [104]. Work by Galvão Wolff et al indicated that IR stimulates endometrial expression of ERs and progesterone receptors (PRs), thereby contributing to the increased occurrence of endometrial proliferative lesions [105].…”
Section: Estrogensmentioning
confidence: 99%
“…Furthermore, an in vitro study showed that insulin directly stimulates aromatase activity in both endometrial glands and stroma, which strongly suggests that hyperinsulinemia caused by IR predisposes to EC by enhancing endogenous endometrial estrogen production [104]. Work by Galvão Wolff et al indicated that IR stimulates endometrial expression of ERs and progesterone receptors (PRs), thereby contributing to the increased occurrence of endometrial proliferative lesions [105].…”
Section: Estrogensmentioning
confidence: 99%